The study of the association between exercise motivation and cardiorespiratory fitness in young students: a systematic review and meta-analysis - Zhou, Fangbing; Wang, Wenlei; Nie, Yuyang; Shao, Chunxue; Ma, Wenxue; Qiu, Wentao; Qu, Guofeng; Gao, Jinchao; Liu, Cong (Frontiers in Psychology, 2025)
BackgroundIn recent years, many studies have shown that exercise motivation is essential for encouraging students to engage in physical activities. Cardiorespiratory function, which is closely related to cardiorespiratory fitness, plays a crucial supportive role in sports, and its level is usually reflected by cardiorespiratory fitness measurements. This study aims to explore the correlation between exercise motivation and cardiorespiratory fitness in young students, analyze the impact of exercise motivation on cardiorespiratory fitness, and investigate the role of cardiorespiratory fitness in the formation of exercise motivation.MethodsFollowing the PRISMA statement, a comprehensive literature search was carried out in six electronic databases from July 1, 2000, to December 1, 2024. The selected studies were strictly quality-assessed, and relevant data were extracted using a standardized form. Then, a meta-analysis was conducted with Stata18 software, along with heterogeneity testing and publication bias assessment.ResultsAfter screening, 11 studies were included. Eight directly explored the correlation between cardiorespiratory fitness and exercise motivation, while the other four investigated the link between physical activity and exercise motivation, suggesting an association between cardiorespiratory fitness and exercise motivation during physical activity. Pearson correlation analysis (11 studies) and multiple regression analysis (7 studies) were used. By combining effect sizes with a random-effects model, the average correlation coefficient was 0.24 (p < 0.001). The average standardized coefficient of exercise motivation on promoting cardiorespiratory fitness was 0.16 (p < 0.001), and that of cardiorespiratory fitness on enhancing exercise motivation was 0.18 (p < 0.001).DiscussionThe results show a significant positive correlation between exercise motivation and cardiorespiratory fitness in young students, with a moderate positive effect on each other. This provides a theoretical basis for improving young students’ cardiorespiratory fitness and exercise motivation. Future research could explore more effective assessment methods to better understand the underlying mechanisms.